PENGARUH JUS BUAH MANGGIS (Garcinia mangostana L.) TERHADAP PROFIL FARMAKOKINETIK PARASETAMOL TIKUS PUTIH JANTAN (Rattus norvegicus) GALUR WISTAR - Emy OKTAVIANI; Mohamad ANDRIE; Bambang WIJIANTO (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2013)
Drug interaction happens when drugs is given together with foods. This research was aimed to observe the effect of mangosteen juice to the paracetamol pharmacokinetic profile in Wistar male white rats. The study used Wistar rats weight of 200-350g. The animals were divided into three groups with the total of the male rats are 15. Group I (paracetamol) was given a single oral paracetamol 9 mg/200gBW. Group II (treatment 1) was given a single oral paracetamol 9 mg/200gBW together with mangosteen juice 2,88 g/200gBW. Group III(treatment 2) was given a single oral paracetamol 9 mg/200gBW together with mangosteen juice 0,66 g/200gBW. The serial blood was collected from tail vein for 9 hours and was analyzed using spectrophotometer UV for unchanged paracetamol. The pharmacokinetic parameters of paracetamol were calculated by recidual method and were analyzed by One Way ANOVA using 95% confidence interval. The difference between groups were analyzed using Post Hoc LSD-test. The results showed that the group II(paracetamol-mangosteen 1) and group III(paracetamol-mangosteen 2) increased of ka, Cpmaks, tmaks, t½ab, ke, t½el, CL, AUC and decreased of ka, ke, and CL. The research showed that mangosteen juice doses 2 give higher decreased metabolism and decreased elimination of paracetamol in rat.